Teacher's teaching practices in the class of mualaf (new convert) - Suhid, Asmawati; Mohd Fakhruddin, Fathiyah; Che Abah, Noreha; Rashed, Zetty Nurzuliana; Ahmad, Abd. Muhsin; Zaremohzzabieh, Zeinab (Canadian Center of Science and Education, 2021)
Education is highly emphasized in Islam because it can guide people to live righteous life according to Islamic law. The same also applies to mualaf or converts, who should be provided with proper education and guidance to perform their duties as true Muslims. In Malaysia, an increasing number of individuals are embracing Islam as their way of life. They are given an education and need to attend classes to ensure that they understand and practice the teachings of Islam properly. Therefore, teachers play an important role in achieving this goal by applying interesting and effective teaching methods. This study was conducted to identify the perceptions of mualaf students on their teachers' teaching practices in the classroom to ensure that they understand and practice what they have learned in class, besides strengthening their faith and morals. A total of 124 mualaf students from two educational institutions in one of the states in Malaysia were involved in this study using quantitative methods. Questionnaires were used to collect data based on the objectives of the study. The results showed that students had a positive perception of the teaching methods used by their teachers. This study also discussed some of the problems faced by mualaf students in their learning process. Overall, the findings of the study indicated that most students have a positive view of their teachers’ teaching. The current findings are expected to provide input to relevant agencies and a guide to improving the quality of teaching for mualafs.